Nonspecific, Acute Pouchitis in Patients With Familial Adenomatous Polyposis: Less Common Than We Think. Issue 6 (3rd May 2022) - Abbass, Mohammad Ali; Lavryk, Olga A.; Hyman, Neil; Liska, David; Kalady, Matthew F.; Church, James
Abstract : BACKGROUND: Nonspecific acute pouchitis is common in patients with ulcerative colitis who undergo IPAA, but there is disagreement about the rate at which this occurs in patients with familial adenomatous polyposis. OBJECTIVE: This study aimed to define the rate at which nonspecific acute pouchitis occurs in patients with familial adenomatous polyposis. SETTING: This study was conducted at a hereditary colorectal cancer center in a large academic medical center. DESIGN: This is a retrospective cohort study using prospectively gathered data. PATIENTS: Patients with familial adenomatous polyposis who have had IPAA were included. INTERVENTIONS: Symptoms, pouchoscopy and pouch radiography, and pouch biopsy were evaluated. MAIN OUTCOME MEASURES: The primary outcomes measured were the presence of nonspecific acute pouchitis and the alternative diagnosis of pouch dysfunction. RESULTS: There were 250 patients with familial adenomatous polyposis who had undergone IPAA; 38 (15.2%) had been labeled as having "pouchitis": 23 men and 15 women. Median age was 55 years (range, 18–90 years). No patient had nonspecific, acute pouchitis as defined by our criteria. In 9 cases, the diagnosis was derived from benign ulcers common in ileal pouches. Stool frequency was the most common symptom associated with the "pouchitis" label, but actual causes for the frequency included poor pouch emptying, poor eating habits, poor bowel habits, and afferent limb syndrome. Median stool frequency was 9, ranging from 4 to 15 per day. Every patient had at least 1 pouch endoscopy, and the median number was 19 per patient (range, 1–21). Nine patients had pouch biopsies to rule out inflammation; all showed chronic active enteritis, a normal finding in ileal pouches. LIMITATIONS: This study was limited by its retrospective nature. CONCLUSIONS: We could not confirm any case of nonspecific acute pouchitis in patients with familial adenomatous polyposis. Those caring for patients with familial adenomatous polyposis who have a pouch should seek causes for pouch-related symptoms other than "pouchitis." See Video Abstract at http://links.lww.com/DCR/B666 . POUCHITIS AGUDA INESPECÍFICA EN PACIENTES CON POLIPOSIS ADENOMATOSA FAMILIAR: MENOS COMÚN DE LO QUE PENSAMOS ANTECEDENTES: La pouchitis aguda e inespecífica es común en pacientes con colitis ulcerativa, sometidos a anastomosis de bolsa ileoanal, pero no hay acuerdo sobre la frecuencia en que se presenta en pacientes con poliposis adenomatosa familiar (PAF). OBJETIVO: Definir la frecuencia en la que se presenta pouchitis aguda inespecífica en pacientes con poliposis adenomatosa familiar. ENTORNO CLINICO: Centro de cáncer colorrectal hereditario en un gran centro médico académico. DISEÑO: Estudio de cohorte retrospectivo utilizando datos recopilados prospectivamente. PACIENTES: Pacientes con poliposis adenomatosa familiar sometidos a bolsa con anastomosis ileoanal. INTERVENCIONES: Síntomas, proctoscopia, radiografía y biopsia de bolsa ileoanal. PRINCIPALES MEDIDAS DE VALORACION: Presencia de pouchitis aguda inespecífica; diagnósticos alternos de disfunción de la bolsa ileal. RESULTADOS: De 250 pacientes con poliposis adenomatosa familiar sometidos a una anastomosis anal de la bolsa ileal; 38 (15, 2%), habían sido etiquetados como "pouchitis", 23 hombres y 15 mujeres. La mediana de edad fue de 55 años (rango de 18 a 90 años). Ningún paciente tuvo pouchitis aguda inespecífica según lo definido por nuestros criterios. En 9 casos el diagnóstico se derivó de úlceras benignas frecuentes en bolsas ileales. La frecuencia de las evacuaciones fue el síntoma más común asociado con la etiqueta "pouchitis", pero las causas reales de la frecuencia, incluyeron un mal vaciado de la bolsa, malos hábitos alimenticios, malos hábitos intestinales y síndrome de asa aferente. La frecuencia media de las evacuaciones fue de 9, con un rango de 4 a 15 por día. A cada paciente se le realizó al menos una endoscopia de la bolsa: la mediana fue de 19 por paciente (rango de 1 a 21). A 9 pacientes se les realizó biopsia de bolsa para descartar inflamación: todos mostraron enteritis activa crónica, un hallazgo normal en las bolsas ileales. LIMITACIONES: Naturaleza retrospectiva del estudio. CONCLUSIONES: No pudimos confirmar ningún caso de pouchitis aguda e inespecífica en pacientes con PAF. Aquellos que atienden a pacientes con PAF con bolsa ileal, deben buscar otras causas para los síntomas relacionados con la bolsa que no sean "pouchitis". Consulte Video Resumen en http://links.lww.com/DCR/B666 . (Traducción—Dr. Fidel Ruiz Healy )